Mir-Let-7i-5p As A Novel Regulator of MYC Gene Expression in Acute Myeloid Leukaemia - Esa, Ezalia; Wan Mohd Nor, Wan Muhammad Farhan Syafiq; Mejia Mohamed, Elsa Haniffah; Lim, Wei-Yue; Zakaria, Zubaidah; Mat Yusoff, Yuslina; Bong, Ivyna Pau Ni; Pung, Yuh-Fen; Fakharuzi, Noor Atiqah; Zain, Shamsul Mohd (Malaysian Applied Biology, 2025)
Acute myeloid leukaemia (AML) is a severe bone marrow malignancy with a high mortality rate. Recent advancements in high-throughput technology and bioinformatics have facilitated the identification of microRNAs (miRNAs) involved in the pathogenesis of AML. This study aimed to investigate the potential role of MicroRNA-let-7i-5p (miR-let-7i-5p) in the progression of AML. MiR-let-7 family has been widely utilised as a tumour inhibitor, suppressing its expression in several types of human cancer. Hence, dysregulation of miR-let-7i-5p is critical to cancer progression. However, the role of miR-let-7i-5p in AML remains unclear. Using the Gene Expression Omnibus (GEO) database, the expression of miR-let-7i-5p in AML patients was investigated. The role of miR-let-7i-5p and its potential target genes in AML was examined using bioinformatic tools. Subsequently, the effect of miR-let-7i-5p was assessed through transfection, followed by the analysis of target gene expression using RT-qPCR. Further investigations employed the MTT and cell cycle assays on the effects of miR-let-7i-5p on AML cell proliferation and cell cycle. According to the GEO database, miR-let-7i-5p was significantly downregulated in AML patients compared to controls. AML development has been associated with miR-let-7i-5p by KEGG pathway analysis. Bioinformatics suggested that miR-let-7i-5p targets MYC in AML cells. Transfection of miR-let-7i-5p into AML cell lines decreased MYC expression, suggesting MYC regulates AML progression. However, MTT and cell cycle assays showed no significant effect of miR-let-7i-5p on AML cell proliferation and cell cycle, indicating the potential involvement of miR-let-7i-5p in alternative pathways in AML pathogenesis. The study highlights the potential significance of miR-let-7i-5p in regulating AML progression.